Measurements of the relative permeability to CO2‐and‐brine multiphase fluid of Paaratte formation at near‐reservoir conditions. Issue 4 (7th May 2021) - Huang, Pengyu; Shen, Luming; Gan, Yixiang; Shen, Yinjie; Du, Dongxing; Yu, Bowei; Maggi, Federico; El‐Zein, Abbas
Abstract: CO2 sequestration in deep saline aquifers is a promising method to reduce atmospheric CO2 . The on‐going CO2 CRC Otway project aims to demonstrate the effectiveness of large‐scale CO2 storage in deep saline formations and to develop new monitoring technologies in Australia. The relative permeability curves are essential for predicting the movements of CO2 and estimate residual trapping in the aquifer during and after injection through numerical simulations. However, studies of relative permeability curves for the Paaratte sandstone at the in situ c onditions are limited. In addition, different rock types in the Paaratte formation can behave differently when CO2 displaces brine. This work reports four relative permeability experiments of CO2 /brine systems using the unsteady‐state core flooding method for different types of rock collected from various depths of Paaratte formations at near‐reservoir conditions. The relative permeability results calculated from the analytical Johnson, Bossler, and Naumann (JBN) method and the numerical history matching method are compared. The JBN method does not calculate the relative permeability accurately for CO2 /brine systems due to the assumptions of incompressible flow, since the CO2 relative permeability results calculated from the JBN method are similar for all the cases. The history matching results show that the brine (water) relative permeability of the core samples with a high fraction of macropores is similar to the measurements for Paaratte formation reported in the literature over a large range of brine (water) saturation. In contrast, the brine relative permeability of the core samples with a high fraction of micropores is considerably higher than that of the core samples with macropores, suggesting better connectivity for the samples with a high fraction of micropores. The new findings will be useful in reservoir‐scale numerical modelings of the Paaratte formation to more accurately predict the movement of CO2 during and after the injection. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd.